Diversity and distribution of Charales (Charophyta) in the Kharkiv Region (CHORNOMORSKI BOTANICAL JOURNAL, 2018)
The results of a study on charophytes (Charales, Charophyta) of different type water bodies on territory of the Siversky Donets river basin (Kharkiv Region) in summer 2018 are presented. They substantially supplemented the previous checklist of the Kharkiv Region Charales. However the findings of Chara braunii, Ch. canescens, Nitella flexilis, N. gracilis and N. syncarpa recorded in the end of ХІХ – at the beginning of ХХ centuries have not been supported by herbarium specimens. Their localities vanished as a result of natural or anthropogenic transformations. Existence of 10 species, namely: Chara connivens, C. contraria, C. globularis, C. intermedia, C. tomentosa, C. vulgaris, Nitella mucronata, Nitellopsis obtusa, Tolypella glomerata and T. prolifera, which have their constant localities in the Kharkiv Region being supported by numerous new findings in recent time. According to a frequency of occurrence the species are denoted as most common (2 species), frequent (4) and rare (4). Some centers of species diversity of Charales have been revealed in the valleys of Siversky Donets River and its tributaries Oskil and Bereka rivers. They are characterized by specific complexes of species determined by a difference in hydrological and hydro-chemical regimes of water bodies situated in Forest-Steppe and Steppe zones within the Kharkiv Region. The complexes of species are represented by Chara globularis, Nitella mucronata, Nitellopsis obtusa in the Siversky Donets valley; Chara contraria, C. intermedia, C. tomentosa, C. vulgaris and Nitellopsis obtusa in the Oskil valley; Chara contraria, C. connivens, C. intermedia, C. vulgaris and Tolypella glomerata in the Bereka valley. The steady or changeable hydrological regime of water bodies, chemical composition, salinity and alkalinity of water are suggested as main factors influencing on diversity and distribution of Charales in the Kharkiv Region.
Keywords: Charales, species diversity, distribution, Kharkiv Region, Ukraine.